Secondary metabolites from the resins of Aloe vera and Commiphora mukul mitigate lipid peroxidation - Rehman Najeeb Ur; Al-Riyami Samia Ahmed; Hussain Hidayat; Ali Amjad; Khan Abdul Latif; Al-Harrasi Ahmed (Acta Pharmaceutica)
Oxidative stress is often considered detrimental for cellular processes and damaging for the lipid bi-layer. Counteracting such stresses with the aid of nature-based chemical constituents can be an ideal therapeutic approach. The current study aimed to investigate the chemical constituents of resins derived from the well-known Aloe vera and less known Commiphora mukul trees and their effect in mitigating the lipid peroxidation (LPO) process. The bio-guided isolation of bio-active fractions from both resins afforded 20 chemical constituents (17 from A. vera and 3 from C. mukul). These compounds belonged to anthraquinones, anthraquinone glycosides, quinones, coumarins, polypodane-type terpenoids and benzene derivatives. Major chemical constituents of the resins of A. vera and C. mukul were from the classes of quinones and terpenoids. Feroxidin (4, from A. vera) showed slightly higher inhibition (IC50 = 201.7 ± 0.9 µmol L−1) than myrrhanone C (18, from C. mukul: IC50 = 210.7 ± 0.0 µmol L−1) and methyl 3-(4-hydroxyphenyl) propionate from A. vera (13, IC50 = 232.9 ± 0.2 µmol L−1) compared to the other compounds. Structure-activity relationship showed that the existence of hydroxyl, methoxy and ether groups might play a major role in countering oxidative stress. To the best of our knowledge, anti-LPO activities of compounds 1–4, 14, 18 and 20 are reported for the first time. Such chemical constituents with high anti-lipid peroxidation activity could be helpful in synthesizing candidate drugs.